2017
DOI: 10.1177/0038038517702600
|View full text |Cite
|
Sign up to set email alerts
|

‘To Try and Gain an Advantage for My Team’: Homophobic and Homosexually Themed Chanting among English Football Fans

Abstract: Association football (soccer) fans are becoming increasingly liberal in their attitudes towards homosexuality. However, the continued presence of homosexually themed chanting – normally interpreted as evidence of homophobia by footballing authorities – has received little academic attention. Through 30 semi-structured interviews with 30 male football fans of various English football clubs, this article uses McCormack’s model of homosexually themed language to investigate the prevalence, triggers and interpreta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
66
2
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 32 publications
(43 reference statements)
10
66
2
3
Order By: Relevance
“…Like many of the respondents in previous studies (McCormack et al ., ; Magrath, ; Sexton, ), the students and teachers in our research suggested that homosexually themed language is more complex than often expressed in academic research or popular media. The use of homosexually themed terms, such as ‘that's so gay’, can be used in a positive fashion, such as a mechanism for bonding between friends.…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…Like many of the respondents in previous studies (McCormack et al ., ; Magrath, ; Sexton, ), the students and teachers in our research suggested that homosexually themed language is more complex than often expressed in academic research or popular media. The use of homosexually themed terms, such as ‘that's so gay’, can be used in a positive fashion, such as a mechanism for bonding between friends.…”
Section: Resultsmentioning
confidence: 61%
“…However, as cultural homophobia has declined, so too has the use of homosexually themed language to wound LGB people (see McCormack, ). Indeed, participants in our research (both staff and students) suggested that homosexually themed language was complex—and rarely employed with intent to wound (Magrath, ). Instead, it served two main purposes: first, as a means of friends bonding, such as the phrase ‘fag hag’ to affectionately describe a female student; or second, as a ‘cathartic expression of dissatisfaction’ (McCormack, 2012, p. 116).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is focused upon the display of sociability and is linked to the private domain, especially marriage and childcare. Connell (2005: 54) identifies sport as the 'leading definer' of masculinity and football in the UK is particularly associated with masculinity due to its association with physical strength, skill and power (Magrath, 2017). Professional sportsmen are held as 'exemplars' of 'hegemonic masculinity' -symbols that have authority despite the fact that most males do not live up to them (Connell and Messerschmidt, 2005: 846).…”
Section: Theoretical Considerations: Connell and The 'Gender Order'mentioning
confidence: 99%
“…When women do participate in traditionally 'masculine' team sports, the media focus on performance-irrelevant aspects such as their private lives or physical looks (see Crossman et al, 2007;Kian et al, 2008). This has a number of potential consequences for the coverage of women's football -a sport which has typically been associated with masculinity (Magrath, 2017). Kian et al (2008) discuss how the exclusion and trivialization of female athletes and women's sports are major themes that consistently emerge in research.…”
Section: Feminist Research On Gender Media and Sportmentioning
confidence: 99%